Performance of Capsicum under Rainshelter - Vezhavendan S (Department of Olericulture, College of Horticulture, 2003)
An experiment was carried out in the Department of Olericulture, College of Horticulture, Vellanikkara, during the rabi (2001) and kharif (2002) seasons to study the performance of capsicum under rain shelter. The experiment was laid out in Completely Randomised Block Design with four replications. Four Capsicum varieties, viz. CA 776, Yolo Wonder, California Wonder, CA 567 and one Fl hybrid Pusa Deepthi were used for the study. The study revealed that the crops grown under rain shelter performed better with respect to all the characters viz. Plant height, 'number of branches, early flowering, early harvest, number of fruits per plant, fruit size, fruit yield per plant, number of seeds per fruit and number of harvests. As like the growing condition, the season also influenced some attributes. Rabi season crop gave better results regarding number of fruits per plant, fruit .yield per plant, number of seeds per fruit, fruit size and number of harvests. Where as kharif crop produced tall plants with larger fruit size. Though tlte variety CA567 gave more yield consistently during both the seasons, the yield was higher under rain shelter condition. CA 776 (CA 776) performed well during rabi but its performance was poor during kharif due to the severe incidence of pest and diseases. Even though the weather parameters like temperature, humidity and light intensity not influenced individually and significantly but Lad cumulative effect, which is evident from the performance of the crop under rain shelter condition. The severe incidence of pest like mite caused reduction in the yield during kharif season under rain shelter.